1985
DOI: 10.3354/meps024261
|View full text |Cite
|
Sign up to set email alerts
|

Byssus-thread formation by the mussel Mytilus edulis: effects of environmental factors

Abstract: Temperature, excision, salinity, tidal regime, and seasonality all affected byssus production in the mussel Myfilus edulisL.; however, the most influential factor studied was agitation. Mussels agitated every 4.5 S produce 15.8 threads ind-' d-l, a rate twice that stimulated by any of the other factors. An acclimation period of up to 2 wk was required for byssus-thread formation to return to that of control mussels after exposure to high temperatures, low salinities and rapid agitation. Byssus-thread productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
66
3

Year Published

1989
1989
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 11 publications
3
66
3
Order By: Relevance
“…Field experiments indicate that 90% of the variation in thread production can be predicted from changes in temperature, wave height and reproductive condition; temperature explains the largest amount of the variation. Similar observations have been made previously (Allen et al, 1976;Clarke and McMahon, 1996c;Young, 1985) suggesting that temperature may be a better predictor of thread production in mussels than wave action. However, it is unknown whether temperature is the underlying mechanism driving this change or another factor that varies concomitantly with temperature.…”
Section: P<0001supporting
confidence: 78%
See 3 more Smart Citations
“…Field experiments indicate that 90% of the variation in thread production can be predicted from changes in temperature, wave height and reproductive condition; temperature explains the largest amount of the variation. Similar observations have been made previously (Allen et al, 1976;Clarke and McMahon, 1996c;Young, 1985) suggesting that temperature may be a better predictor of thread production in mussels than wave action. However, it is unknown whether temperature is the underlying mechanism driving this change or another factor that varies concomitantly with temperature.…”
Section: P<0001supporting
confidence: 78%
“…These results are not surprising, as previous studies have also found that agitation, the combination of byssal loading and acceleration, produces conflicting responses in mussels. Young (1985) observed a marked increase in thread production following the agitation of M. edulis, whereas, in D. polymorpha, byssal thread production was found to be both reduced and enhanced in response to agitation (Clarke and McMahon, 1996b;Rajagopal et al, 1996). The inconsistent response to byssal loading across months observed in this study is most probably due to the variable amount of load that was experienced by each individual mussel, which was directly proportional to the number of threads produced by the mussel and placed in tension.…”
Section: P<0001contrasting
confidence: 41%
See 2 more Smart Citations
“…Mussels respond to their flow environment by altering their attachment strength. In the laboratory, water agitation increases the number of byssal threads produced (Young 1985). In the field, attachment strength varies with location in a mussel bed (Witman & Suchanek 1984, Bell & Gosline 1997, wave exposure of the site (Witman & Suchanek 1984), and, seasonally with wind conditions (Price 1982).…”
Section: Introductionmentioning
confidence: 99%